Reasons for non-adherence to obesity treatment in children and adolescents - Thaïs Florence D. Nogueira; Mariana Porto Zambon (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE To analyze the reasons for non-adherence to follow-up at a specialized outpatient clinic for obese children and adolescents. METHODS Descriptive study of 41 patients, including information from medical records and phone recorded questionnaires which included two open questions and eight closed ones: reason for abandonment, financial and structural difficulties (distance and transport costs), relationship with professionals, obesity evolution, treatment continuity, knowledge of difficulties and obesity complications. RESULTS Among the interviewees, 29.3% reported that adherence to the program spent too much time and it was difficult to adjust consultations to patientsâ€(tm) and parentsâ€(tm) schedules. Other reasons were: childrenâ€(tm)s refusal to follow treatment (29.3%), dissatisfaction with the result (17.0%), treatment in another health service (12.2%), difficulty in schedule return (7.3%) and delay in attendance (4.9%). All denied any relationship problems with professionals. Among the respondents, 85.4% said they are still overweight. They reported hurdles to appropriate nutrition and physical activity (financial difficulty, lack of parentsâ€(tm) time, physical limitation and insecure neighborhood). Among the 33 respondents that reported difficulties with obesity, 78.8% had emotional disorders such as bullying, anxiety and irritability; 24.2% presented fatigue, 15.1% had difficulty in dressing up and 15.1% referred pain. The knowledge of the following complications prevailed: cardicac (97.6%), aesthetic (90.2%), psychological (90.2%), presence of obesity in adulthood (90.2%), diabetes (85.4%) and cancer (31.4%). CONCLUSIONS According to the results, it is possible to create weight control public programs that are easier to access, encouraging appropriate nutrition and physical activities in order to achieve obesity prevention.